On Peculiarities of Wind Conditions in Antarctic Peninsula region - Shven, N. I.; Klock, S. V. (Ukrainian Antarctic Journal, 2005)
Long-term changes of wind and thermal regime in area of Antarctic Peninsula are considered. Dependence of annual mean wind speed increase for last decades at the Vernadsky station on reduction of the atmospheric pressure caused by the southward displacement of cyclones is discussed. Infrequent cases of breeze circulation at the Vernadsky Station are found out at presence of corresponding contrast of temperatures between surface of ocean and land.